2015
DOI: 10.1108/ijaim-12-2014-0082
|View full text |Cite
|
Sign up to set email alerts
|

Has the harmonisation of accounting practices improved? Evidence from South Asia

Abstract: Purpose -This paper aims to examine whether the level of harmonization of accounting measurement practices in three South Asian countries -Bangladesh, India and Pakistan -has improved since 1998 as a result of the changes, in recent years, globally in accounting measurement practices due to the substantial efforts of the International Accounting Standards Board (IASB). South Asian countries have taken a number of steps and made changes in accounting regulations to support the IASB's harmonization programme. De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…This new drive of harmonisation has caused many accounting scholars to focus on the measurement of de-facto harmonisation (Ahmed and Ali 2015;Bayerlein and Al-Farooque 2012, Jones and Finely 2011, Van der Tas (1998, which are even confined to developed countries. Many researchers now believe that harmonisation can be achieved only at the point of practices (de-facto harmonisation).…”
Section: 0mentioning
confidence: 99%
See 1 more Smart Citation
“…This new drive of harmonisation has caused many accounting scholars to focus on the measurement of de-facto harmonisation (Ahmed and Ali 2015;Bayerlein and Al-Farooque 2012, Jones and Finely 2011, Van der Tas (1998, which are even confined to developed countries. Many researchers now believe that harmonisation can be achieved only at the point of practices (de-facto harmonisation).…”
Section: 0mentioning
confidence: 99%
“…Klibi and Kossentini (2014) also highlighted that the use of IFRS impact stock market development in emerging countries. Other scholars such as Campa and Donnelly (2016), and Cormier et al (2015) has provided evidence on how IFRS improve reporting quality. For instance, Tawiah and Muhaheranwa (2015) reported that Indian companies that use IFRS provide quality accounting information than those using the local standards.…”
Section: 0mentioning
confidence: 99%
“…IFRS adoption could be identified as one of the standard-setting strategies used in many emerging economies (Ben Othman and Kossentini, 2015;Perera and Baydoun, 2007). Several empirical studies have examined the relevance of IFRS in South Asian countries 57 Moderating effect of IFRS adoption (Ahmed and Ali, 2015;Bhattacharjee, 2009;Chakrabarty, 2014;Hossain et al, 2015;Zaman Mir and Shiraz Rahaman, 2005).…”
Section: Ifrs Adoption As a Moderatormentioning
confidence: 99%
“…Unlike these states' one-step implementation of IFRS, there are also countries that have chosen to gradually integrate IFRS. India is one such instance and has launched a gradual method of compliance with international AS (Ahmed, Kamran, and Ali, Muhammad., 2015). IASB argues that 130 nations have a public dedication to its worldwide execution in having one standard of accounts.…”
Section: The Current State Of Ifrs Implementation Process At Global Lmentioning
confidence: 99%